Categorical regularization: Discussion of article by Tutz and Gertheiss. (June 2016) - Agresti, Alan
This is a discussion of the article 'Regularized Regression for Categorical Data' by Tutz and Gertheiss. As part of the discussion, I raise some questions that may suggest future research work.